2012
DOI: 10.1371/journal.pone.0034766
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Analysis on Bamboos following the Fukushima Nuclear Accident

Abstract: In response to contamination from the recent Fukushima nuclear accident, we conducted radionuclide analysis on bamboos sampled from six sites within a 25 to 980 km radius of the Fukushima Daiichi nuclear power plant. Maximum activity concentrations of radiocesium 134Cs and 137Cs in samples from Fukushima city, 65 km away from the Fukushima Daiichi plant, were in excess of 71 and 79 kBq/kg, dry weight (DW), respectively. In Kashiwa city, 195 km away from the Fukushima Daiichi, the sample concentrations were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Numerical simulation showed that the radionuclides derived from FNPP1 circulated around the Northern Hemisphere (Stohl et al, 2012), and the fission products were actually detected in aerosol, gaseous, rain and snow samples collected in North America (e.g., Bowyer et al, 2011;Leon et al, 2011), Europe (e.g., Bossew et al, 2012Masson et al, 2011), central Russia (Bolsunovsky & Dementyev, 2011;Melgunov et al, 2012) and Taiwan (Huh et al, 2012). The radionuclides emitted from FNPP1 were also detected from terrestrial biota not only in Japan (e.g., Hashimoto et al, 2012;Higaki et al, 2012;Tagami et al, 2012) but also in North America (Thakur et al, 2012) and Europe (Cosma et al, 2011;Pittauerova et al, 2011). As compared with the terrestrial research, however, studies on the influences of the FNPP1 accident to marine biota have been scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Numerical simulation showed that the radionuclides derived from FNPP1 circulated around the Northern Hemisphere (Stohl et al, 2012), and the fission products were actually detected in aerosol, gaseous, rain and snow samples collected in North America (e.g., Bowyer et al, 2011;Leon et al, 2011), Europe (e.g., Bossew et al, 2012Masson et al, 2011), central Russia (Bolsunovsky & Dementyev, 2011;Melgunov et al, 2012) and Taiwan (Huh et al, 2012). The radionuclides emitted from FNPP1 were also detected from terrestrial biota not only in Japan (e.g., Hashimoto et al, 2012;Higaki et al, 2012;Tagami et al, 2012) but also in North America (Thakur et al, 2012) and Europe (Cosma et al, 2011;Pittauerova et al, 2011). As compared with the terrestrial research, however, studies on the influences of the FNPP1 accident to marine biota have been scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Because the underground stem-root system of bamboo mainly exists in the soil layers, we cannot eliminate the possibility of root absorption. However, we previously reported higher radiocesium activities in mature leaves than in young ones in bamboo plants 25–195 km from the Fukushima Daiichi nuclear plant 4 months after the nuclear accident [7] , suggesting direct deposition of radiocesium fallout onto mature leaves. In addition, after the Chernobyl nuclear accident, studies of thyme plants ( Origanum vulgare L.) in Turkey suggested the importance of foliar absorption of radiocesium rather than root uptake [19] .…”
Section: Discussionmentioning
confidence: 76%
“…The Fukushima-derived radiocesium ( 134 Cs and 137 Cs) largely fell on land in the Tohoku and Kanto regions of Japan [2] , [3] and in the Northwest Pacific Ocean [4] , [5] . Radiocesium contamination in agricultural and woody plants has been reported [6] , [7] , [8] . Radiocesium contamination of food crops has become of prime interest, especially for residents in the affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of radionuclide was conducted on bamboo sampled from six sites within a 25-to 980-km radius of the Fukushima plant in July to August 2011. 4 Strikingly high concentrations of radiocesium-134 and -137 activity were detected in mature leaves from Fukushima city (65 km from the Fukushima plant), in excess of 71 and 79 kBq/kg of dry weight (DW). In Kashiwa city (195 km from the plant), sample concentrations were in excess of 3.4 and 4.3 kBq/kg DW.…”
Section: Depopulation With Rapid Aging In Minamisoma City After the Fmentioning
confidence: 99%